FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEPUTUSAN PETANI UNTUK BERALIH DARI USAHATANI BAWANG MERAH KE USAHATANI BAWANG DAUN DI DESA TORONGREJO KECAMATAN JUNREJO KOTA BATU - Imra Atus Sholikah; Farida Syakir; Sri Hindarti (Program Studi Agribisnis, 2019)
AbstractThis research to determine differences income between shalot and leaf onion farmers in Torongrejo Village and to determine factors that influence farmer’s decision to change. Determination of research location with purposive sampling in Torongrejo Village, Junrejo subdistrict, Batu City using stratified random sampling method of 30 samples of shallot and scallion farmers. The analist data method used of the analisys T test and using the logit method. The results showed that the income of shallots and onion farmers significantly different. Factors that influence the shift of shallot farmers to onion are education, land, labor, income, family members and capital.Keywords: shallot, switch decision.